2021
DOI: 10.1080/15226514.2021.1900062
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of heavy metal and nutrients removal in Canna indica and Oryza sativa L. based constructed wetlands for piggery effluent treatment in north-central Nigeria

Abstract: Batch-fed horizontal sub-surface flow constructed wetlands (HssFCW) were developed to compare the potential of Canna indica and Oryza sativa L. in removing heavy metals and nutrients from piggery effluent. Piggery effluent samples were characterized for nutrients (N and P) and metals (Mg, Al, Ca and Fe) before and after introducing them to the HssFCW with hydraulic retention time (HRT) of 3 days and operational flowrate of 0.014 m 3 /day. Three sets of constructed wetlands (CWs) were monitored during the dry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In a study on treatment of piggery effluent, BCF was reported to be 1.1 for Fe, 1.0 for Mg, 0.2 for Al, 0.9 for Ca, 0.4 for Zn and 0.7 for Mn. In the same study, TF was 0.7 for Fe, 0.8 for Mg, 0.6 for Al, 0.9 for Ca, 0.8 for Zn and 0.8 for Mn [89]. These results shows the potential of Canna indica for removal of heavy metals from aquatic systems [80].…”
Section: Bcf =supporting
confidence: 53%
“…In a study on treatment of piggery effluent, BCF was reported to be 1.1 for Fe, 1.0 for Mg, 0.2 for Al, 0.9 for Ca, 0.4 for Zn and 0.7 for Mn. In the same study, TF was 0.7 for Fe, 0.8 for Mg, 0.6 for Al, 0.9 for Ca, 0.8 for Zn and 0.8 for Mn [89]. These results shows the potential of Canna indica for removal of heavy metals from aquatic systems [80].…”
Section: Bcf =supporting
confidence: 53%
“…Ref. [41], in their studies, also found that the planted systems were more efficient than the unplanted systems. Overall, the metal concentrations in the treated effluents of the planted constructed wetlands were within the allowable WBG levels.…”
Section: Heavy Metals Removalmentioning
confidence: 93%
“…The efficiency of rice plants in phytoremediation of PTHMs from water or soil has been reported by various researchers (Liu et al 2007;Evangelou et al 2015;Pajević et al 2016;Yan et al 2020). Further, Rice is being used in numerous research due to its vast range of adaptability to different environmental conditions and potential to tolerate abiotic stress (Liu et al 2007;Bharagava et al 2008;Satpathy et al 2014;Olawale et al 2021;Lakshmi et al 2021). Earlier, the potential of the rice plant to remediate heavy metals like Cd, Pb, and Fe contaminated soil and water have been studied by various researchers (Liu et al 2007;Satpathy et al 2014;Olawale et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Rice is being used in numerous research due to its vast range of adaptability to different environmental conditions and potential to tolerate abiotic stress (Liu et al 2007;Bharagava et al 2008;Satpathy et al 2014;Olawale et al 2021;Lakshmi et al 2021). Earlier, the potential of the rice plant to remediate heavy metals like Cd, Pb, and Fe contaminated soil and water have been studied by various researchers (Liu et al 2007;Satpathy et al 2014;Olawale et al 2021). India has high production of rice and many farmers irrigate their crop plants with industrial wastewater having a high load of toxic compounds including PTHMs due to the non-availability of alternative sources of irrigation.…”
Section: Introductionmentioning
confidence: 99%